The Anthropocene beyond stratigraphy – towards a normative imperative for science and universities - Allerberger, Franziska; Stötter, Johann (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
The Anthropocene, regardless of which interpretation of content and time one follows, is characterised by the fact that humans have become one, if not the global driver and creator. The increasingly intensive interventions in the Earth system result in global challenges that increasingly call the future of all humankind into question. A way out of this crisis situation only seems possible by means of a comprehensive socio-ecological transformation. In the context of this dualism between challenges and solution options, science is expected and demanded to take on a central role in overcoming the existential crisis. In order to fulfil this social responsibility, the science system must transform itself and overcome inherent lock-ins that have so far prevented significant impacts beyond the academic world. In the sense of a ‘normative imperative for science in general and universities in particular’ (also see Allerberger and Stötter 2022, this issue), we aim to provide starting points for such a self-transformation in relation to four different fields of action of universities. These include transdisciplinary and transformative research, among others, to fulfil the Third Mission, overcoming excellence fetishism, teaching that empowers students to deal with challenges in a solution-oriented way, and a completely different attitude towards the governance of universities, including changes in the dimensions of culture, structure, communication and cooperation.